Methods of Sentinel Lymph Node Identification in Auricular Melanoma. Issue 12 (20th December 2021) - Noorbakhsh, Seth; Papageorge, Marianna; Maina, Renee M.; Baumann, Raymond; Moores, Craig; Weiss, Sarah A.; Pucar, Darko; Ariyan, Stephan; Olino, Kelly; Clune, James
Abstract : Background: Sentinel lymph node biopsy is used to evaluate for micrometastasis in auricular melanoma. However, lymphatic drainage patterns of the ear are not well defined and predicting the location of sentinel nodes can be difficult. The goal of this study was to define the lymphatic drainage patterns of the ear and to compare multiple modalities of sentinel node identification. Methods: A retrospective review of a prospectively maintained database evaluated 80 patients with auricular melanoma who underwent sentinel lymph node biopsy by comparing preoperative imaging with intraoperative identification of sentinel nodes. Patients were placed into two cohorts, based on the modality of preoperative imaging: (1) planar lymphoscintigraphy only (n = 63) and (2) single-photon emission computerized tomography combined with computerized tomography (SPECT-CT) only (n = 17). Sites of preoperative mapping and sites of intraoperative identification were recorded as parotid/preauricular, mastoid/postauricular, and/or cervical. Results: In patients that underwent planar lymphoscintigraphy preoperatively (n = 63), significantly more sentinel nodes were identified intraoperatively than were mapped preoperatively in both the parotid/preauricular ( P = 0.0017) and mastoid/postauricular ( P = 0.0047) regions. Thirty-two nodes were identified intraoperatively that were not mapped preoperatively in the planar lymphoscintigraphy group (n = 63), two of which were positive for micrometastatic disease. In contrast, there were no discrepancies between preoperative mapping and intraoperative identification of sentinel nodes in the SPECT-CT group (n = 17). Conclusions: SPECT-CT is more accurate than planar lymphoscintigraphy for the preoperative identification of draining sentinel lymph nodes in auricular melanoma. If SPECT-CT is not available, planar lymphoscintigraphy can also be used safely, but careful intraoperative evaluation, even in basins not mapped by lymphoscintigraphy, must be performed to avoid missed sentinel nodes.